2018
DOI: 10.1108/ijqrm-01-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Are customers ready to accept revenue management practices in the restaurant industry?

Abstract: Purpose -The purpose of this research is to investigate the application of revenue management practices to the restaurant industry. We want to observe customers' readiness to accept revenue management practices based on price variation, booking policy, table management, and control duration. We also want to measure the impact of these four practices on customer patronage intention. Design/methodology/approach -A survey was conducted with 251 respondents. As we had several latent variables, we used partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Within the context of restaurants, perceived fairness is a diner’s belief that the outcome of a meal is reasonable and that the cost and benefit of the dining transaction are commensurate for both the restaurant and the diner (Bolton et al , 2003). Researchers have found that perceived fairness is an antecedent of both purchase intention and repurchase intention (Etemad-Sajadi, 2018; Grewal et al , 2004; Haws and Bearden, 2006; Taylor and Kimes, 2010; Xia et al , 2004), as consumers are less likely to patronize companies perceived to be unfair (Kahneman et al , 1986a; Kimes and Wirtz, 2002). Customers may even punish an unfair firm by traveling an additional distance to purchase at another firm and avoid patronizing a firm known to conduct business unfairly (Kahneman et al , 1986b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the context of restaurants, perceived fairness is a diner’s belief that the outcome of a meal is reasonable and that the cost and benefit of the dining transaction are commensurate for both the restaurant and the diner (Bolton et al , 2003). Researchers have found that perceived fairness is an antecedent of both purchase intention and repurchase intention (Etemad-Sajadi, 2018; Grewal et al , 2004; Haws and Bearden, 2006; Taylor and Kimes, 2010; Xia et al , 2004), as consumers are less likely to patronize companies perceived to be unfair (Kahneman et al , 1986a; Kimes and Wirtz, 2002). Customers may even punish an unfair firm by traveling an additional distance to purchase at another firm and avoid patronizing a firm known to conduct business unfairly (Kahneman et al , 1986b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accepting reservations is a well-established practice in the foodservice industry that assists restaurants in reducing arrival uncertainty to effect duration control (Kimes, 2004). Past empirical studies have investigated various elements of restaurant reservations including overbooking (Tse and Poon, 2017), imposing booking conditions onto guests (Etemad-Sajadi, 2018) and charging fees (Etemad-Sajadi, 2018; Kimes and Wirtz, 2016). Etemad-Sajadi (2018) determined that guests perceive it is fair for restaurants to add reservation stipulations such as requiring a credit card to confirm a reservation, charging for no-shows or late arrivals and canceling reservations of late arriving guests.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Having identified that the key concepts of menu management consist of menu analysis and revenue management, researchers and practitioners who approach this topic from a practical perspective may express scepticism and limitations of applying such concepts within a practical setting. The successful application of menu analysis and revenue management techniques require consistent records of sales data, well defined strategy, knowledgeable and committed teamwork within a restaurant to execute successful menu analysis and revenue management techniques (Etemad-Sajadi, 2018;Kimes & Beard, 2013;Raab & Zemke, 2016). The above literature review presents the major concepts that are commonly practiced within menu management.…”
Section: Limitations and Applicability Of Existing Methodsmentioning
confidence: 99%
“…It is known that one of the basic concepts defining luxury restaurants is high price (Lee and Hwang, 2011). The price change at various times during the day or during the week affects customers' intentions to go that restaurants frequently (Etemad, 2018). The most important topic that Michelin star restaurant's managers should pay attention to is price-performance management.…”
Section: Michelin Referencementioning
confidence: 99%